Trigonometric Solutions of WDVV Equations and Generalized Calogero-Moser-Sutherland Systems - Feigin, M.V. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We consider trigonometric solutions of WDVV equations and derive geometric conditions when a collection of vectors with multiplicities determines such a solution. We incorporate these conditions into the notion of trigonometric Veselov system (∨-system) and we determine all trigonometric ∨-systems with up to five vectors. We show that generalized Calogero-Moser-Sutherland operator admits a factorized eigenfunction if and only if it corresponds to the trigonometric ∨-system; this inverts a one-way implication observed by Veselov for the rational solutions.